2016
DOI: 10.1002/pbc.26154
|View full text |Cite
|
Sign up to set email alerts
|

A single‐center experience with undifferentiated embryonal sarcoma of the liver

Abstract: Undifferentiated embryonal sarcoma of the liver (UESL) is a rare aggressive mesenchymal pediatric tumor. Previously, reported outcomes have been very poor. Here we report a single center experience of 5 patients with UESL treated with upfront gross total resection and adjuvant chemotherapy. We have a median follow up of 8 years with a range from 5 to 19 years with 100% EFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
19
1
Order By: Relevance
“…3 Mathias et al report upto a median of eight years of survival after multimodal management. 16 Similarly, May et al reported successful treatment of these patients using a chemotherapy regimen of vincristine, cyclophosphamide and actinomycin-D to encounter any residual tumor cells after surgical resection. 33 For unresectable cases, neoadjuvant chemotherapy may be used.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3 Mathias et al report upto a median of eight years of survival after multimodal management. 16 Similarly, May et al reported successful treatment of these patients using a chemotherapy regimen of vincristine, cyclophosphamide and actinomycin-D to encounter any residual tumor cells after surgical resection. 33 For unresectable cases, neoadjuvant chemotherapy may be used.…”
Section: Discussionmentioning
confidence: 98%
“…14,15 A retrospective study conducted by Mathias et al, shows a 100% event-free (EFS) and 100% overall survival (OS) with no recurrence or secondary malignancy over a median of eight years of follow-up. 16 However, the mortality ensues from recurrent or metastatic disease. 17,18 In the upcoming section, we discuss an interesting case of undifferentiated embryonal sarcoma of the liver in a seven-year-old male child.…”
Section: Introductionmentioning
confidence: 99%
“…In the original report of 31 patients with UESL by Stocker and Ishak, only six patients were alive without any evidence of the disease [ 7 ]. Over the past couple of years, mounting evidence suggests that radical surgical resection of the tumor supplemented by adjuvant chemotherapy leads to an overall improvement in the survival of these patients [ 19 ]. Herein, we report encouraging results of following this protocol in patients with UESL.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, it presents in children from the age of six to ten and shows no gender predilection. It is considered to be the third most common malignant hepatic tumor in childhood, after hepatoblastoma and hepatocellular carcinoma, accounting for approximately 9–15% of all pediatric liver tumors, with an incidence of one case per million people per year [ 30 , 158 , 159 , 160 , 161 , 162 , 163 ].…”
Section: Malignant Tumors In School-aged Children and Adolescentsmentioning
confidence: 99%